Frequency dependence of fading statistics for ultrawideband systems - Malik, W; Edwards, D; Stevens, C (2007)
The variation of channel fading and dispersion statistics between the ultrawideband (UWB) channel subbands is characterized experimentally. Within the FCC-allocated UWB frequency range (3.1-10.6 GHz), the multipath characteristics in various subbands are found to be highly dissimilar. It is demonstrated that the higher subbands suffer greater attenuation, and the rms delay spread varies significantly with the center frequency. The impact of this variation on multiband-OFDM UWB system performance is evaluated, and a large performance variation across the band is reported. © 2007 IEEE.